Variations in hypophyseal responsiveness to synthetic GnRH-induced LH releaseand reproductive performance in dairy buffaloes with luteal activity during earlypostpartum period - SINGH, A K; BRAR, P S; GANDOTRA, V K; NANDA, A S; PRAKASH, B S (The Indian Journal of Animal Sciences, 2011)
Elevated luteal activity immediately following parturition reduces the reproductive performance in terms of prolonged anestrus that results in serious economic constraints to buffalo breeders. The present study was undertaken with the objective to investigate the changes in pituitary responsiveness to synthetic GnRH in 15 lactating buffaloes at 25–35 days post-partum. On the basis of progesterone profile for at least 2 consecutive samples, they were categorized into 2 groups i.e. with elevated luteal activity (plasma P4 > 1.0 ng/ml; n = 9) and reduced luteal activity (plasma P4 < 1.0 ng/ ml; n = 6). All the buffaloes were subjected to an injection of GnRH (20 μg buserelin acetate) intravenously. Heparinized venous blood samples were collected at 15 min intervals for 2 h before and up to 4 h following GnRH injection for luteinizing hormone (LH) estimation. Pretreatment LH profiles were similar in elevated (0.6±0.1 ng/ml) and reduced (0.4±0.1 ng/ml) luteal phase buffaloes. Rise in LH concentration following GnRH administration was observed in all but 1 buffalo with high progesterone level. The maximum LH release and area under LH curve in the remaining buffaloes with elevated luteal activity were significantly less compared to their reduced counterparts (18.3±3.9 versus 26.9±3.3 ng/ml and 1690.3±229.0 versus 2268.7±235.1 mm2), respectively. The second aim of the study was to assess the postpartum reproduction in buffaloes of both the groups. Plasma progesterone estimations were done at the start of study, and every 7 days thereafter up to 7 weeks. Rectal palpation was used to diagnose pregnancy. The results revealed that postpartum intervals to first oestrus and conception were significantly longer in buffaloes with high than with low progesterone level. In the meantime, reduced luteal phase buffaloes compared to elevated ones increased the overall conception rates by 10.2%, respectively. In conclusion, buffaloes with elevated compared to reduce luteal activity had suppressed pituitary responsiveness to synthetic GnRH challenge and poor reproductive performance during early postpartum period.